The Race between Tax Enforcement and Tax Planning: Evidence from a Natural Experiment in Chile - Sebastián Bustos; Dina Pomeranz; Juan Carlos Suárez Serrato; José Vila-Belda; Gabriel Zucman (Center for Economic Studies and ifo Institute (CESifo), 2023)
Profit shifting by multinational corporations is thought to reduce tax revenue around the world. While transfer pricing regulations are meant to curtail profit shifting, there have been rising concerns that a sophisticated tax advisory industry can limit their effectiveness. This paper provides a comprehensive analysis of how firms and tax advisors respond to the introduction of standard regulations aimed at limiting profit shifting. Using administrative tax and customs data from Chile in difference-in-differences event-study designs, we find that the reform was ineffective in reducing multinationals' transfers to lower-tax countries and did not significantly raise tax payments. At the same time, interviews with tax advisors reveal a drastic increase in tax advisory services. The qualitative interviews also allow us to identify and then quantitatively confirm a common tax planning strategy in response to the reform. These results illustrate that when enforcement can be circumvented by sophisticated tax planning, it can benefit tax consultants at the expense of tax authorities and taxpayers.
Keywords: H25; H26; H32; 330